The Value of Character Education in Short Stories in the High Grade Elementary School Indonesian Language Module and Its Relevance to Learning at SDN 03 Tiumang: Nilai Pendidikan Karakter dalam Cerpen Pada Modul Bahasa Indonesia SD Kelas Tinggi dan Relevansinya Terhadap Pembelajaran di SDN 03 Tiumang - Gyimnastiar, Abdullah (Journal of Vocational Education and Information Technology (JVEIT), 2023)
This research is motivated by the eroding phenomena of the value of character education that occur in the school environment at this time. Therefore, this study aims to describe the values ​​of character education contained in the short stories in the high grade Indonesian Language Module at SDN 03 Tiumang and their relevance to the school environment. This type of research is qualitative using descriptive analysis method. The data sources of this research are short stories in the Indonesian Language Module class IV and V SDN 03 Tiumang, namely the short story Dayu and Ornamental Fish, Air Pollution, Working Together in Diversity and Differences Are Not Barriers.. Data collection techniques by: (1) Reading and understanding short stories, (2) searching for data containing character education values ​​in short stories, (3) inventorying, identifying, and classifying data with character education values. The results of this study indicate that there are 18 data, namely the value of discipline character education (3), the value of responsible character education (4), the value of independent character education (2), the value of environmental care character education (1), the value of creative character education (3) , the value of religious character education (3), the value of tolerance character education (2). So there are 18 sentences of character education values ​​in the short story.